Investigation of failure mechanism in tensile loading of Cu-AISI4140 steel joints fabricated by spark plasma welding - Mehdi Naderi; Mohammad Reza Toroghinejad; Ahmad Kermanpur (Journal of Materials Research and Technology)
In this study, failure mechanism under tensile loading of the joint interfaces Cu-AISI4140 steel fabricated by spark plasma welding (SPW) is investigated. The SPW process was conducted at 700 °C and a pressure of 20 MPa for durations of 5, 15, 30, and 60 min. Tensile loading was applied to evaluate mechanical properties of the joints. Microstructural analyses of the joints were performed using scanning electron microscopy, while the fracture surfaces of the samples after tensile testing were examined using field emission scanning electron microscopy. Grazing incidence X-ray diffraction was employed to identify phases at the joint interface on fracture surface of the joints. The results revealed that the SPW process facilitated the forced mixing of Cu in steel and Fe in Cu, without formation of any inter-metallic compound at the joint interface. Additionally, strength of the joint formed over a 60-min duration approached that of Cu. Examination of the fracture surfaces indicated brittle failure in the elastic zone for joints formed over a 5-min duration. As the process time increased to 15 and 30 min, brittle and ductile ruptures occurred, respectively, before reaching the maximum stress in the engineering stress-strain curve. In the joint formed over a 60-min duration, rupture did not occur at the joint interface before reaching the maximum stress in the engineering stress-strain curve. Instead, with the development of micro-necking at numerous areas of the joint interface, ductile failure occurred after reaching the maximum stress.